Mass Preferences for the Free Movement of People in Africa: A Public Opinion Analysis of 36 Countries. Issue 1 (March 2022) - Gordon, Steven
The African Union (AU) has identified opening borders to cross-national mobility as a prime strategic goal, and AU leaders have heralded regional free movement as a vital tool for economic growth and skills development on the continent. Little, however, is known about the level (or determinants) of public support for opening borders in the AU. This article examines public preferences for free movement among 36 African countries. Using data from the sixth round of the Afrobarometer Survey (N = 53, 935), the analysis presented here shows a remarkable degree of variation in mobility-related preferences both within and between nations, and explores whether a utilitarian model of attitude formation can explain mass preferences for open borders across African countries. Investigating both macro- and micro-level determinants of public attitudes toward border control, the article shows that the utilitarian model had greater explanatory power at the macro-level than at the micro-level. In addition, some support was found for identity-based predictors (e.g., nationalism versus cosmopolitanism) of support for free movement. These outcomes point toward a new way of understanding public attitudes toward regional integration in Africa. The article concludes by discussing future avenues of public opinion research toward mobility rights on the continent and beyond.